2020
DOI: 10.1051/0004-6361/202037745
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Proxima with ESPRESSO

Abstract: Context. The discovery of Proxima b marked one of the most important milestones in exoplanetary science in recent years. Yet the limited precision of the available radial velocity data and the difficulty in modelling the stellar activity calls for a confirmation of the Earth-mass planet. Aims. We aim to confirm the presence of Proxima b using independent measurements obtained with the new ESPRESSO spectrograph, and refine the planetary parameters taking advantage of its improved precision. Methods. We analysed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(47 citation statements)
references
References 66 publications
1
45
0
1
Order By: Relevance
“…It has been argued that CCF FWHM and log HK measurements should both behave, to first order, as the convective blueshift suppression term in the method, which in turn is a close proxy for the integrated active region coverage on the visible stellar hemisphere (Rajpaul et al 2015); indeed, it has been shown in practice that the CCF FWHM can be a good tracer of photometric flux (e.g. Suárez Mascareño et al 2020). Thus, as we did not have photometric measurements of HD 13808 available, we chose to interpret the FWHM as a proxy for the flux Ψ( ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been argued that CCF FWHM and log HK measurements should both behave, to first order, as the convective blueshift suppression term in the method, which in turn is a close proxy for the integrated active region coverage on the visible stellar hemisphere (Rajpaul et al 2015); indeed, it has been shown in practice that the CCF FWHM can be a good tracer of photometric flux (e.g. Suárez Mascareño et al 2020). Thus, as we did not have photometric measurements of HD 13808 available, we chose to interpret the FWHM as a proxy for the flux Ψ( ).…”
Section: Methodsmentioning
confidence: 99%
“…Successful exo-Earth discovery therefore requires both more sophisticated models of stellar variability and the improved RV precision, long-term stability, and dense observational sampling from a next-generation spectrograph (Wright & Robertson 2017) such as the Echelle SPectrograph for Rocky Exoplanets and Stable Spectroscopic Observations (ESPRESSO; Pepe et al 2013Pepe et al , 2021Damasso et al 2020;Suárez Mascareño et al 2020), NEID (Allen et al 2018), EXtreme PREcision Spectrometer (EXPRES; Jurgenson et al 2016;Blackman et al 2020;Brewer et al 2020;Petersburg et al 2020), HARPS3 (Thompson et al 2016), or GMT Consortium Large Earth Finder (G-CLEF; Szentgyorgyi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…With radial velocity (RV) signatures of the smallest planets having semi-amplitudes of meters per second, or lower, high resolution stable spectrographs, such as HARPS (Mayor et al 2003) and HARPS-N (Cosentino et al 2012) have been essential to further characterise these systems, precisely determining planetary masses and measuring the physical and chemical properties of the host stars. Newer-generation spectrographs, like ESPRESSO (Pepe et al 2014(Pepe et al , 2020, will deliver long-term RV precision of 10 cm/s, a factor of at least 5 better than HARPS-N, and are thus expected to perform even better (as shown recently in Suárez Mascareño et al 2020).…”
Section: Introductionmentioning
confidence: 94%
“…similar wavelength ranges as the HARPS-N chromatic RVs (except a longer range for the red RVS thanks to the extended wavelength range of ESPRESSO). Details on the extraction can be found in Suárez Mascareño et al (2020). The HARPS-N and ESPRESSO 1 RV time series overlap between October 2018 and February 2019.…”
Section: Espresso Spectroscopymentioning
confidence: 99%